2012
DOI: 10.1016/j.parkreldis.2012.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Health comorbidities and cognition in 1948 patients with idiopathic Parkinson's disease

Abstract: This study with a large cohort of PD patients provides evidence for a small detrimental influence of specific health comorbidities, particularly heart/circulatory and diabetes, on general measures of cognition. This effect is present, above and beyond the influences of basic demographic information (age), duration and staging of PD, and medication status. Future studies involving more refined cognitive indices and direct assessment of comorbidities are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
5
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 31 publications
(45 reference statements)
4
31
5
4
Order By: Relevance
“…Our findings of independent DM-related contributions to cognitive impairment in PD adds to the emerging literature that medical comorbidities can aggravate the clinical course of primary neurodegenerative disorders, such as PD (32, 33). Cognitive impairment in PD likely reflects the cumulative effects of heterogeneous processes, including independent effects of nigrostriatal dopaminergic and forebrain cholinergic denervations (18).…”
Section: Discussionsupporting
confidence: 64%
“…Our findings of independent DM-related contributions to cognitive impairment in PD adds to the emerging literature that medical comorbidities can aggravate the clinical course of primary neurodegenerative disorders, such as PD (32, 33). Cognitive impairment in PD likely reflects the cumulative effects of heterogeneous processes, including independent effects of nigrostriatal dopaminergic and forebrain cholinergic denervations (18).…”
Section: Discussionsupporting
confidence: 64%
“…A high nocturnal blood pressure is also associated with an increased prevalence of end-organ damage (Berganzo et al, 2013). Moreover, a large cross-sectional study with a cohort of PD patients provided evidence for an influence of specific comorbidities, particularly heart/circulatory comorbidities and diabetes, on general measures of cognition (Jones et al, 2012). The onset of OSAS may probably help to explain the increased risk of cardiovascular disease and CVD in PD and parkinsonism patients.…”
Section: F Crosta Et Almentioning
confidence: 99%
“…The US Centers for Disease Control and prevention (CDC) estimate a national prevalence of diabetes of 9.4% [15]. A cross-sectional study of PD patients ( n = 1948) receiving care at non-VA National Parkinson Foundation Clinical Centers of Excellence is in line with this estimate showed a 9% prevalence of Diabetes and an overall 36.3% prevalence of “heart/circulation” comorbidities [2]. A similar survey conducted in large national VA PD sample ( n = 14,530) showed a self-reported prevalence of Diabetes to be much higher (22.3%).…”
Section: Discussionmentioning
confidence: 86%
“…Cardiovascular risk factors are common comorbidities in PD [2] and are a leading source of chronic disability worldwide. We previously reported that diabetes in PD associates with postural instability and gait difficulty as well as cognitive impairment [3, 4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation